Modeling Ca2+ signals: understanding Ca2+ regulatory networks in cells - Ca2+ stores: mitochondria, models of spatially non-uniform Ca2+ signals, applications to analysis of experimental results - Friel, David (Henry Stewart Talks, 2021)
FCCP-sensitive Ca2+ stores, The mitochondrial uniporter (MCU), Mitochondrial Ca2+ flux, Spatially nonuniform Ca2+ signals, Spatial hierarchy of Ca2+ signals, The diffusion equation, Ca2+ responses in spherically symmetrical cells, Methods for analyzing Ca2+ handling properties in intact cells, Developing an experimentally based model of Ca2+ dynamics in sympathetic neurons